Discovery of a Second Eclipsing, ​​​​​Bursting Neutron Star Low-mass X-Ray Binary in the Globular Cluster Terzan 6 - Maureen van den Berg; Jeroen Homan; Craig O. Heinke; David A. Pooley; Rudy Wijnands; Arash Bahramian; James C. A. Miller-Jones (The Astrophysical Journal, 2024)
We have analyzed Chandra and Suzaku observations of the globular cluster Terzan 6, made when the recurrent transient GRS 1747–312 was in quiescence. Our analysis reveals the presence of a second eclipsing, bursting neutron star low-mass X-ray binary in the central regions of the cluster, in addition to GRS 1747–312. The new source, which we name Terzan 6 X2, is located only ∼0.″7 away from GRS 1747–312 in the 2021 Chandra images. The detection of a 5.14 ks long eclipse in the light curve of X2 at a time not predicted by the ephemeris of GRS 1747–312 confirms that it is an unrelated source. Using the Suzaku light curve from 2009, which, in addition to a type I X-ray burst, also showed an eclipse-like feature, we constrain the orbital period to be longer than 16.27 hr. The 0.5–10 keV luminosities of X2 vary in the range of ∼0.24–5.9 × 10 ^34 erg s ^−1 on timescales of months to years. We have identified a plausible optical counterpart of X2 in Hubble Space Telescope F606W and F814W images. This star varied by 2.7 mag in V _606 between epochs separated by years. In the cluster color–magnitude diagram, the variable counterpart lies in the blue-straggler region when it was optically bright, about 1.1–1.7 mag above the main-sequence turn-off. From the orbital period–density relation of Roche-lobe filling stars, we find the mass-donor radius to be ≳0.8 R _⊙ .